Identifikasi Miskonsepsi Fisika Siswa Menggunakan Two Tier Diagnostic Test - Sitinjak, Erni Kusrini; Marbun, Juliaster; Lumbangaol, Sudirman.T.P.; Panigrahi, Rashmi Ranjan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to determine the misconceptions of class X students on the concept of Temperature and Heat using a two-tier multiple choice diagnostic test at SMA Bersama Berastagi Private. This research is included in the descriptive qualitative research. The population in this study were students of class X MIA. The sample in this study were 68 people. Diagnostic test data were collected using a two-tier multiple choice to identify students' understanding of concepts into conceptual understanding, misconceptions, guessing and not understanding concepts. Based on the research results obtained from a two-tier multiple choice diagnostic test on students of class X MIA1 and X MIA3 SMA Bersama Berastagi Private High School, misconceptions were identified in each sub-concept of the concepts of Temperature and Heat. The sequence of sub-materials that identified misconceptions from those with the highest to the lowest proportions was as follows: black principle (77.94%) and the lowest misconception occurred in the heat sub-matter (4.41%).